Advanced Optimal PSO, Fuzzy and PI Controller with PMSM and WTGS at 5Hz Side of Generation and 50Hz Side of Grid - Salam Waley Shneen; Chengxiong Mao; Dan Wang (Institute of Advanced Engineering and Science, 2016)
To use different control systems, Like Classical PI Controller, Expert System, Fuzzy Logic Controller and Optimization PSO Controller. It used to control for PMSM which worked in integration system to Wind Energy. Wind Energy content of wind turbine, PMSM, Rectifier, DC bus, Inverter, Filter, Load and Grid. In the first step, to run the PMSM with different speeds to get different frequency to selected the frequency in side of generation with the rated speed. Second step, solve the mathematical equation to use different values of wind speed with selected (15,20 m/s and less than with more than 15&20m/s). Third step, Calculation the power generation with wind speed (15 m/5 & 20 m/s). Fourth step, using these component system Rectifier, DC bus, Inverter, Filter, Load & Grid with WTGS & PMSM. Final step, use different control systems, Like Classical PI Controller, Expert System Fuzzy Logic Controller and Optimization PSO Controller With PMSM to analysis all results after using the simulation model of proposed variable speed based WECS. The wind turbine coupled with PMSM.A closed loop control system with a PI control,Fuzzy, PSO in the speed loop with current controllers .The simulation circuits for PMSM, inverter, speed and current controllers include all realistic components of the drive system. These results also confirmed that the transient torque and current never exceed the maximum permissible value.